2015
DOI: 10.2139/ssrn.2788601
|View full text |Cite
|
Sign up to set email alerts
|

Upskilling: Do Employers Demand Greater Skill When Skilled Workers Are Plentiful?

Abstract: Using a large database of online job postings, we demonstrate that employee skill requirements rise when there is a larger supply of relevant job seekers. We identify this effect using variation across time, occupations, and places, which allows us to control for potentially confounding factors. We further exploit the natural experiment arising from troop withdrawals from Iraq and Afghanistan over this period as a shock to local, occupation-specific labor supply. Our estimates imply that the increase in nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Indeed, postsecondary credentials—whether it be a certificate, an associate's degree, or a bachelor's degree—have become a requirement for many jobs that previously required only a high school degree (Modestino, Shoag, & Ballance, ). At the same time, employer expectations for work readiness, communication, and other soft skills have risen—qualifications that are difficult for youth to demonstrate without a track record of work experience (Harrington et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, postsecondary credentials—whether it be a certificate, an associate's degree, or a bachelor's degree—have become a requirement for many jobs that previously required only a high school degree (Modestino, Shoag, & Ballance, ). At the same time, employer expectations for work readiness, communication, and other soft skills have risen—qualifications that are difficult for youth to demonstrate without a track record of work experience (Harrington et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…2 This massive increase in required skills raised concerns that the U.S. labor market faced a structural and persistent mismatch between workers' skills and firms' needs. Here and in Modestino, Shoag, and Ballance (2014), we argue that a significant portion of this increase in employer skill requirements reflects strategic or opportunistic 3 upskilling, whereby firms used slack labor markets as an opportunity to hire more skilled workers, potentially increasing productivity. Rather than mismatch causing unemployment, we claim that a significant portion of the observed changes in skill requirements during the Great Recession resulted from employers' response to loose labor markets.…”
mentioning
confidence: 83%
“…Previous work examining this dynamic found that employers raised education and experience requirements within occupations, and even within firm and job titles (Modestino, Shoag, andBallance 2014, Hershbein andKahn 2016). This growth in skill levels within occupations has colloquially become known as upskilling.…”
mentioning
confidence: 99%
“…Although there is significant enthusiasm for apprenticeship models in the U.S. resulting in rapid growth, this modern incarnation of apprenticeship design is relatively new, and there is not much evidence that they are actually beneficial in the U.S. economic system [21]. An abundance of research exists from countries such as Germany, Switzerland, the United Kingdom, and Australia [18,[22][23][24]. For example, Hanushek, Schwert, Woessmann, and Zhang [25] conducted a large, quasi-experimental study of the long-term effects of vocational education in 11 European countries.…”
Section: Research-based Evidence About Apprenticeshipsmentioning
confidence: 99%
“…Research suggests that participation in CTE can improve students' employment outcomes [23,30]. Furthermore, studies found that associate's degrees and other post-secondary certificates are linked to increased lifetime earnings and career growth [22,30].…”
Section: Drawbacks Of Apprenticeship-the Case For Higher Ed Alignmentmentioning
confidence: 99%